Does the level of financial development matter for the fiscal response? A PSTR approach for the EU and selected OECD countries - Bettina Bökemeier; Andreea Stoian; Benjamin Owusu (Bielefeld University, Faculty of Business Administration and Economics, 2023)
This paper empirically studies the role of financial development in the fiscal response function by distinguishing high and low financial development regimes based on a data driven selection mechanism and investigating two groups of economies, European Union (EU) members and OECD countries from 2000 to 2019. Applying the panel smooth transition regression to separate two regimes based on the status of financial development we find a threshold of about 0.60 of financial development (FD) on average in the EU, a little higher in the OECD. Our results indicate that the stance of financial development matters for fiscal policy design and business cycle behavior. The response effectively differs for low financial development regime situations compared to high financial development regimes, both, with regard to debt sustainability as well as the output gap in the EU and the OECD, too. While in the low FD regime debt indicates to be sustainable and the business cycle performs pro-cyclically, in high FD regimes the picture changes to a more mixed behavior including debt non-sustainability and counter-cyclical output manner. This holds true for both, the EU as well as the OECD. Thus, our results indicate that financial markets do fuel (fiscal) policy behavior. Too much financial development can influence particularly the debt reaction and the business cycle.
urn:nbn:de:0070-pub-29690772
Keywords: H63; E62; 330; Debt sustainability; fiscal response function; financial development; panel smooth transition regression